5x+2(-3x-2)=1-6x

Simple and best practice solution for 5x+2(-3x-2)=1-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+2(-3x-2)=1-6x equation:


Simplifying
5x + 2(-3x + -2) = 1 + -6x

Reorder the terms:
5x + 2(-2 + -3x) = 1 + -6x
5x + (-2 * 2 + -3x * 2) = 1 + -6x
5x + (-4 + -6x) = 1 + -6x

Reorder the terms:
-4 + 5x + -6x = 1 + -6x

Combine like terms: 5x + -6x = -1x
-4 + -1x = 1 + -6x

Solving
-4 + -1x = 1 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-4 + -1x + 6x = 1 + -6x + 6x

Combine like terms: -1x + 6x = 5x
-4 + 5x = 1 + -6x + 6x

Combine like terms: -6x + 6x = 0
-4 + 5x = 1 + 0
-4 + 5x = 1

Add '4' to each side of the equation.
-4 + 4 + 5x = 1 + 4

Combine like terms: -4 + 4 = 0
0 + 5x = 1 + 4
5x = 1 + 4

Combine like terms: 1 + 4 = 5
5x = 5

Divide each side by '5'.
x = 1

Simplifying
x = 1

See similar equations:

| -(7y-1)-(-6y+6)=7 | | 7a-3(a-1)=51 | | 0=6x^2-23x+20 | | 7/8-5/8=2 | | 2x+4(x-6)=12 | | 9x+3x=20 | | 62=7x+6 | | 138=11x+17 | | 16(x-7)=-4(x+38) | | 6(x+8)=5x+54 | | 6x^2+58x+105=0 | | 14=2/3(9y-15) | | 7(2x-8)=2(3x-8) | | 3(a-16)=2a-16 | | 5-3a+5a=-8+6+9a | | 30-2(x-4)=2-11x | | 5-3a+5a+-8+6+9a= | | 6x(6-3)=2(7x-9) | | 7(x+5x)-3(6x-x)=6(4x-3x)-9(4x+5) | | 9x+27=6x+60 | | 20x^2-30x=2x+45 | | 1+-6y=1+4y | | 53=3x+14 | | -156-10x=9x+15 | | 0.7n-1.5+7.3n= | | 3x+11=-22-8x | | 799x=1003 | | 0.5x^2+9x+3.2=0 | | 12x(120+360)12=17 | | 3x-5=-43 | | 8x^2+54x-14=0 | | 0.4x=1.2 |

Equations solver categories